(untitled) (KYAMC Journal, 2019)
Background: Oral submucous fibrosis is a chronic debilitating disease of the oral cavity characterized by inflammation and progressive fibrosis of the submucosal tissues. It is a precancerous condition of the oral mucosa characterized by excessive production of collagen leading to inelasticity of the oral mucosa and atrophic changes of the epithelium. A wide range of treatment including drug management, surgical therapy, and physiotherapy have been attempted till date, with varying degrees of benefit, but none have been able to cure this disease. Objectives: To evaluate the efficacy of Intralesional ’Dexamethasone Plus Hyaluronidase plus Placental extract in comparison to intralesional injections of ’Dexamethasone plus Hyaluronidase in the management of OSMF patients. Materials and Methods: Thirty patients with OSMF were randomly divided equally into two groups. Fifteen patients in ’Dexamethasone plus Hyaluronidase(Group-I)’ group received biweekly intralesional injections of Dexamethasone (4mg/ml) plus Hyaluronidase 1500 IU in buccal mucosa for a period of 12 weeks. Other Fifteen patients in’Dexamethasone plus Hyaluronidase plus placental extract (Group-II)’ group received biweekly intralesional injections of Dexamethasone (4mg/ml) plus Hyaluronidase 1500 IU plus placental extract in buccal mucosa for a period of 12 weeks. Parameters taken in the study were burning sensation, and mouth opening. Descriptive statistics, paired t test and unpaired t test were used for statistical analysis. Results: The pre- and post-treatment Differences were found to be statistically not significant for both the groups (p<0.001) and for both the treatment outcomes. Conclusion: In the present study, the efficacy of Intralesional ’Dexamethasone Plus Hyaluronidase plus Placental extract’ showed no superiority over intralesional injections of ’Dexamethasone plus Hyaluronidase’ in the management of OSMF patients. KYAMC Journal Vol. 10, No.-2, July 2019, Page 77-80